Successful Use of Plasma Exchange in the Treatment of Corticosteroid-Refractory Eosinophilic Granulomatosis with Polyangiitis Associated with Gastrointestinal Manifestations - Kohei Tsujimoto; Masato Yagita; Masashi Taniguchi; Masaaki Fujita (Case Reports in Immunology)
We describe the case of a 33-year-old woman having corticosteroid-refractory eosinophilic granulomatosis with polyangiitis (EGPA) who presented with abdominal pain and responded dramatically to plasma exchange. Eosinophilia, asthma history, neuropathy, pulmonary infiltrates, and paranasal sinus abnormalities confirmed the diagnosis of EGPA. Treatment was initiated with 1 g/day of methylprednisolone pulse therapy for 3 days followed by 60 mg/day of intravenous prednisolone without relieving abdominal pain. Then, plasma exchange was performed thrice. Abdominal pain disappeared after the first plasma exchange. Indication of plasma exchange for EGPA remains controversial; however, it may represent a valid option in cases with gastrointestinal involvement.